Articulatory and acoustic variation in Polish palatalised retroflexes compared with plain ones. (January 2023) - Lorenc, Anita; Żygis, Marzena; Mik, Łukasz; Pape, Daniel; Sóskuthy, Márton
Abstract: The present paper investigates articulatory and acoustic variation in Polish palatalised retroflex sibilants compared with their plain counterparts. It tests the hypothesis advanced by Hamann (2003: 44) that palatalised retroflexes are non-existent and that retroflexes in Polish change to palato-alveolars [ʃ ʒ t͡ʃ d͡ʒ] when being palatalised. Based on articulatory data from 20 speakers we provide evidence that at least part of the data (53.5%) are palatalised retroflexes [ʂʲ ʐʲ ʈ͡ʂʲ ɖ͡ʐʲ]. The plain counterparts are shown to be retroflex, as proposed by Hamann (2003). Our averaged results indicate that both palatalised and plain retroflexes show a convex tongue shape. However, individual data reveals a wide range of realisations, from a bunched dorsum to flat and even hollowed tongue shapes. Taking this variability into account, we propose a new tongue shape classification based on Heron's Formula – i.e. concave, slightly concave, flat, convex and slightly convex. The different tongue shapes are also visualised in the form of videos created using GAMMs. Regarding acoustic results, our analysis reveals that the strongest correlate of palatalised retroflex sibilants is longer duration of frication in palatalised sibilants followed by higher Centre of Gravity (COG) and m1 spectral slope.